Optimization and prediction of paver block properties with ceramic waste as fine aggregate using response surface methodology - G. Uday Kiran; Nakkeeran G.; Dipankar Roy; George Uwadiegwu Alaneme (Scientific Reports)
Abstract The ceramic industry produces a significant volume of ceramic waste (CW), representing around 20–30% of its the entire output. The waste mostly comes from challenges noticed in the manufacturing process, overproduction, and damage to products. Considering the substantial worldwide production of ceramics, it is crucial to efficiently handle and recycle this waste to promote sustainability efforts. This study explores the conversion of ceramic waste into fine aggregates suitable for the production of paver blocks. Currently, a variety of assessments are being conducted to determine the effectiveness of these enhanced paver blocks. The evaluations involve aspects like compressive strength, water absorption (WA), dry density, flow table measurements, ultrasonic pulse velocity (UPV), and rebound hammer tests. The results indicate that replacing natural aggregates with up to 30% CW significantly improves compressive strength (CS) and Rebound results from tests. This study provides useful information into optimising the content of CW in paver blocks, contributing to the development of sustainable and economical construction materials. Furthermore, it focusses on minimising landfill waste and preserving natural resources.